Implementasi Rule Base System dan Fuzzy Logic Artifical Intelligence pada Game Kartu Capsa - Pangkatodi, Edo; Liliana, Liliana; Budhi, Gregorius Satia (Jurnal Infra, 2016)
In the era of globalization today, science and technology is developing very fast, particularly in entertainment media, specifically in the gaming world. Today, games are not only used as an entertainment, but also can be used as an alternative in the world of work, education, and even sports. In the world of gaming, artificial intelligence, or AI is a factor that cannot be separated. With the right methods and the specific rules of the AI can walk like a human being doing a job. So it is not only in the gaming world alone, AI can also be used in other fields that require AI computing systems for example inÂ technological development.The system is using Unity5 program with the programming language C#, with AI rule base and fuzzy used, the AI expected to have enough ability to be an opponent for players who use this application.Based on testing that has been done, these applications can run smoothly, AI can run and can follow rules of the game and follow the mindset that have been established. But the way of thinking AI still fairly few and need to be developed more.